Analisis Kemampuan Literasi Matematis Pada Materi Sistem Persamaan Linear Tiga Variabel (SPLTV) Siswa SMA - Qiyamul Wusto; Asep Sujana; Rusdian Rifa'i (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
The purpose of this study is to examine high school students’ mathematical literacy in understanding the topic of Three-Variable Linear Equation Systems (SPLTV). Mathematical literacy encompasses the ability to formulate problems, apply mathematical concepts, and interpret results within various real-life contexts. This competence plays a crucial role in supporting students’ problem-solving skills in everyday situations. The study employed a qualitative descriptive method with research subjects consisting of tenth-grade students from a senior high school. The instruments used included a mathematical literacy test and semi-structured interviews. The analysis revealed that students’ levels of mathematical literacy varied, with most experiencing difficulties in connecting contextual problems to appropriate mathematical representations. Therefore, the implementation of learning models that foster critical thinking and deepen conceptual understanding of mathematics is necessary.